Pelatihan membuat hantaran pengantin bagi kelompok ibu-ibu di Kelurahan Batua Makassar - Rosmiaty Rosmiaty; St. Aisyah; Srikandi Srikandi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purpose of this activity is to provide additionalknowledge for women in ORW 5 of Batua village in Manggalasub-district about productive activities which can be their newskill in making wedding gifts (erang-erang) that can bedeveloped in their neighbourhood. The method used in thisworkshop were introduction to productive businesses, trainingand practice. The workshop took place in ORW 5 Batua,Manggala sub-district of Makassar. Activities started withsocialization, giving material, practice and making a follow-upplan. Participants enthusiastically participated in the activitieswith the guidance of the PKM team from the lecturers andstudents of PKK FT UNM, the participants managed to makebeautiful wedding gifts and established the wedding giftsbusiness manager in the neighbourhood of participants.